Effects of Moderate Alcohol Consumption on Platelet Function, Tissue-Type Plasminogen Activator and Plasminogen Activator Inhibitor - Veenastra, J; Kluft, C; Ockhuizen, Th; Pol, H v d; Wedel, M; Schaafsma, G (Thrombosis and Haemostasis, 1990)
Short-term effects of moderate alcohol consumption on platelet function, tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI) were studied in two age groups of volunteers (20–30 and 45–55 years), each consisting of eight healthy males. The alcohol (30 g in red port and wine) was consumed during a standard dinner. Two blood samples were drawn: one in the postprandial phase, and one the next morning after fasting overnight. Alcohol consumption tended to increase platelet aggregation and production of hydroxy fatty acids, reduced plasma t-PA activity and increased PAI activity in the postprandial phase. After the overnight fast the effects on t-PA and PAI had disappeared whereas at that time alcohol consumption tended to decrease platelet function. The effects of alcohol on t-PA and PAI activity appeared mainly in the older age group, whereas the t-PA activity in this group was already much lower, irrespective of alcohol consumption.